Modulators of 14-3-3 Protein-Protein Interactions - Stevers, Loes M; Sijbesma, Eline; Botta, Maurizio; MacKintosh, Carol; Obsil, Tomas; Landrieu, Isabelle; Cau, Ylenia; Wilson, Andrew J; Karawajczyk, Anna; Eickhoff, Jan; Davis, Jeremy; Hann, Michael; et al. (Journal of medicinal chemistry, 2018)
Direct interactions between proteins are essential for the regulation of their functions in biological pathways. Targeting the complex network of protein-protein interactions (PPIs) has now been widely recognized as an attractive means to therapeutically intervene in disease states. Even though this is a challenging endeavor and PPIs have long been regarded as "undruggable" targets, the last two decades have seen an increasing number of successful examples of PPI modulators, resulting in growing interest in this field. PPI modulation requires novel approaches and the integrated efforts of multiple disciplines to be a fruitful strategy. This perspective focuses on the hub-protein 14-3-3, which has several hundred identified protein interaction partners, and is therefore involved in a wide range of cellular processes and diseases. Here, we aim to provide an integrated overview of the approaches explored for the modulation of 14-3-3 PPIs and review the examples resulting from these efforts in both inhibiting and stabilizing specific 14-3-3 protein complexes by small molecules, peptide mimetics, and natural products.